FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2013 – 2015) - Greace Angelina Simangunsong; Rita Anugerah; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of company classification, company’s profitabiliy, solvability, profit or loss, company size, size of public accountant firms, and auditor opinion on audit report lag. The population in this study is companies listed on The Indonesian Stock Exchange in 2013 until 2015. The sampel are collected using purposive sampling method and then result 30 companies become the sampel. Types of data is secondary data and the method of data analysis used multiple linear regressions analysis by using SPSS Windows Ver 17. The result of this study indicated that company classification, solvability, company size, and auditor opinion significantly affect audit report lag with significant value < 0, 05. Meanwhile, company’s profitability, profit or loss, and size of public accountant firms have no affect audit report lag with significant value > 0, 05. Result of determination (R2 ) is 0, 372, it means that the overall effect of independent variables against audit report lag is 37, 2% meanwhile the remaining amounted 62, 8% is influenced by the other independent variables that not used in this study.Keywords : Company Classification, Company’s Profitability, Solvability, Profit or Loss, Company Size, Size of Public Accountant Firms, Auditor Opinion, and Audit Report Lag.